Simultaneous Determination of Danshensu, Protocatechuic Acid, Protocatechuic Aldehyde, Rosmarinic Acid and Salvianolic Acid B in Three Processing Products of White Flower Salvia miltiorrhiza by HPLC - Li, Yuqin; You, Guirong; Duan, Rui; Liu, Ke; Wang, Decai (Asian Journal of Chemistry, 2013)
A reversed-phase high performance liquid chromatographic method was established for the simultaneous determination of five water-soluble components in three processing products of white flower Radix Salvia miltiorrhiza. The analysis was carried on a Yilite C18 column (250 mm × 4.6 mm, 5 μm). The mobile phase was a mixture of methanol and 0.5 % glacial acetic acid, employing gradient elution at a flow rate of 1 mL min-1. Detection wavelength was at 286 nm. Regression equations revealed good linear relationship between the peak areas of the compounds and their concentrations (correlation coefficients: 0.9990-0.9999). The recoveries were between 98.91 and 104.4 %. The results indicated that protocatechuic aicd wasn’t detected in the three processed products and the rest four contents presented the fresh < the wine fried < the carbonizing and provided the theory foundation for pharmacy and clinic.